Integration of Affinity Selection–Mass Spectrometry and Functional Cell-Based Assays to Rapidly Triage Druggable Target Space within the NF-κB Pathway. (July 2016) - Kutilek, Victoria D.; Andrews, Christine L.; Richards, Matthew P.; Xu, Zangwei; Sun, Tianxiao; Chen, Yiping; Hashke, Andrew; Smotrov, Nadya; Fernandez, Rafael; Nickbarg, Elliott B.; Chamberlin, Chad; Sauvagnat, Berengere; et al.
The primary objective of early drug discovery is to associate druggable target space with a desired phenotype. The inability to efficiently associate these often leads to failure early in the drug discovery process. In this proof-of-concept study, the most tractable starting points for drug discovery within the NF-κB pathway model system were identified by integrating affinity selection–mass spectrometry (AS-MS) with functional cellular assays. The AS-MS platform Automated Ligand Identification System (ALIS) was used to rapidly screen 15 NF-κB proteins in parallel against large-compound libraries. ALIS identified 382 target-selective compounds binding to 14 of the 15 proteins. Without any chemical optimization, 22 of the 382 target-selective compounds exhibited a cellular phenotype consistent with the respective target associated in ALIS. Further studies on structurally related compounds distinguished two chemical series that exhibited a preliminary structure-activity relationship and confirmed target-driven cellular activity to NF-κB1/p105 and TRAF5, respectively. These two series represent new drug discovery opportunities for chemical optimization. The results described herein demonstrate the power of combining ALIS with cell functional assays in a high-throughput, target-based approach to determine the most tractable drug discovery opportunities within a pathway.